Bullying among Students in Islamic Boarding Schools: Types, Risk Factors, and Prevention Strategies - Riati Sri Hartini; Yunita Aryani; Desdiani Desdiani (Indonesian Journal of Global Health Research, 2026)
Bullying does not only occur in public schools, but is also commonly found in Islamic boarding schools. Several studies indicate that 61–73% of students experience various forms of bullying, such as violence, extortion, intimidation, and theft. This study investigates the forms, risk factors, and prevention strategies of bullying in Islamic boarding schools (pesantren) in Depok, West Java, Indonesia. A descriptive cross-sectional design was applied involving 51 santri aged 8–15 years from elementary to high school levels, selected through purposive sampling. Data were collected using a 30-item questionnaire documenting bullying experiences, with validity established through theory-based content development and face validity, covering verbal, physical, and sexual bullying perpetrated by peers, teachers, and parents. Descriptive statistics, Chi-square, and Mann–Whitney U tests were employed for analysis. Verbal bullying emerged as the most prevalent form, followed by physical and sexual bullying. Peers were reported more frequently as perpetrators than teachers or parents. A significant association was found between gender and specific types of bullying (p < 0.05). Younger students were significantly more exposed to verbal bullying (p < 0.05). The majority of victims were in early to middle adolescence, a developmental stage marked by heightened susceptibility to peer influence. Bullying remains a critical issue in pesantren settings, involving various perpetrators. Effective prevention should address age and gender differences and the distinctive social context of boarding schools. Enhancing awareness, supervision, and institutional policies is crucial to ensure a safe and supportive learning environment.